2009
DOI: 10.1111/j.1753-6405.2009.00364.x
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in licensee, police and public opinions regarding interventions to reduce alcohol‐related harm associated with licensed premises

Abstract: Licensees were less likely than police and members of the public to agree they were responsible for reducing alcohol-related harm resulting from drinking at their premises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Twenty-one studies were included in the review [6,15,36-54,61-65]. Fifteen of the studies measure public opinion Australia-wide, and the remaining six were conducted in New South Wales (NSW), the Northern Territory (NT), Victoria, and Western Australia (WA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one studies were included in the review [6,15,36-54,61-65]. Fifteen of the studies measure public opinion Australia-wide, and the remaining six were conducted in New South Wales (NSW), the Northern Territory (NT), Victoria, and Western Australia (WA).…”
Section: Resultsmentioning
confidence: 99%
“…Support is highest for initiatives which are directed towards licensees. A large nation-wide survey and a small NSW study conducted in 2007 found that more than four-fifths of Australians and three-quarters of rural NSW residents support stricter regulation, enforcement and penalties for irresponsible serving of alcohol [36,41,44]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, upstream interventions hold strong potential; in this case, information posters could be placed in nightclub washrooms, a technique used in antismoking campaigns 45. However, offender-targeted campaigns have been shown in the literature to have minimal effect on offender opinions or behaviours, and the management at alcohol-serving establishments may be reluctant to engage in campaigns that may discourage consumption 46 47. Conversely, the WHO recommends campaigns targeting the cultural norms that promote violence, with an emphasis on youth education 48.…”
Section: Implications For Prevention and Controlmentioning
confidence: 99%
“…These are the implicit mechanisms, which it is important to draw out, and for which Realism is such a powerful tool. For me the other mechanisms, those theories within the literature (Cherpitel, 2007;Graham & Homel, 2008;Havard, Shakeshaft, & Sanson-Fisher, 2008;Hawkins, Sanson-Fisher, Shakeshaft, & Webb, 2009;Palk, Davey, & Freeman, 2010), came later.…”
Section: The Personal Processmentioning
confidence: 99%